User Satisfaction with the Semeton LH Chatbot: An Integrated TAM and DeLone-McLean Approach - Lisa Ria Fitriani; Sofiansyah Fadli; Jihadul Akbar (Asosiasi Doktor Sistem Informasi Indonesia, 2026)
Digital transformation in public services has encouraged the adoption of chatbots as effective and efficient tools for communication and information delivery. The Central Lombok Regency Environmental Agency developed the Semeton LH chatbot to improve public access to environmental service information. This study aims to analyze user satisfaction with the Semeton LH chatbot by integrating the Technology Acceptance Model (TAM) and the DeLone and McLean Information Systems Success Model. A quantitative approach was employed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS, based on data collected from 96 respondents. The measurement model evaluation indicates that several indicators met validity and reliability criteria; however, some constructs still showed limitations in convergent and discriminant validity, particularly in the Average Variance Extracted (AVE) and Heterotrait-Monotrait Ratio (HTMT) values. Therefore, the structural findings should be interpreted cautiously. The results show that Attitude Toward Using (ATU) has a positive and significant effect on Behavioral Intention to Use (BI) and User Satisfaction (US). In addition, Perceived Ease of Use (PEOU) and Perceived Usefulness (PU) significantly influence ATU. Overall, user satisfaction is primarily shaped by positive attitudes formed through perceived ease of use and perceived usefulness.